Fischer–Tropsch synthetic wastewater treatment with Fe/Mn@CH: Catalytic ozonation and process evaluation - Guo, Lei; Xiao, Zhiqiang; Sun, Wenquan; Xu, Hao; Xu, Yanhua; Zheng, Huaili; Sun, Yongjun (Separation and purification technology, 2021)
[Display omitted] •Fe-Mn@CH with high catalytic activity was prepared.•The organic matter is transformed into protein-like and tryptophan-like substances.•Ozone catalytic oxidation process is closer to the secondary reaction kinetics.•A multi-level-gray relational evaluation model is established. In this study, the honeycomb ceramic catalyst Fe/Mn@CH with high catalytic activity was prepared. The effect of preparation conditions on the catalytic performance of Fe/Mn@CH was systematically studied. Scanning electron microscope; X-ray energy spectrum analysis; X-ray diffraction; specific surface area, pore distribution and adsorption performance analysis; X-ray fluorescence spectroscopy; and X-ray photoelectron spectroscopy were performed to analyze the structural characteristics of the catalyst. The optimal working conditions of the catalytic ozonation system for the degradation of Fischer–Tropsch synthesis wastewater were also studied. The metal elements Fe and Mn were successfully loaded on the surface of the honeycomb ceramic carrier in the form of α-MnO2 and α-Fe2O3 oxides. The optimal COD removal rate could reach 64.37% at pH of 9, ozone dosage of 6 g/h, Fe/Mn@CH dosage of 50 g/300 mL, and reaction time of 60 min. The specific mechanism of catalytic ozonation in the presence of tert-butanol was explored through ultraviolet absorption spectroscopy and three-dimensional fluorescence spectroscopy. The COD removal efficiency for Fischer–Tropsch synthesis wastewater was analyzed on the basis of catalytic oxidation reaction kinetics. Finally, a multilevel gray correlation evaluation model was established for the quantitative evaluation of the ozonation catalytic oxidation of Fischer–Tropsch wastewater.